What Drives Bank Lending Spreads and Collateral Requirements in the Kyrgyz Republic - Ruxandra Teodoru, Iulia (Washington, D.C. : International Monetary Fund, 2020)
Limited access to finance and its high cost have contributed to relatively low levels of private investment and subpar growth in the Kyrgyz Republic. Interest rate spreads have moderated in recent years, but remain high from both a regional and global perspective. At the same time, collateral requirements applied by banks are onerous and also constrain the quantity of credit supplied. This paper identifies a range of factors that could lower spreads in the Kyrgyz Republic: more competition, higher capital, lower credit risk, larger loan size, lower deposit rates and external funding costs, as well as a stronger legal framework. Lower operating costs appear critical to reduce relatively higher spreads for small and medium-sized banks. At the same time, a stronger legal framework and greater transparency on borrowers' creditworthiness would help reduce the high collateral requirements. Reforms in all these areas would support greater financial inclusion in the aftermath of the pandemic, and could thus be a key source of sustainable and inclusive growth in the Kyrgyz Republic.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet